KEUNGGULAN MANAJEMEN GAYA JEPANG, KOREA SELATAN, CINA, AMERIKA SERIKAT DAN INDONESIA SEBAGAI TOLAK UKUR PERSAINGAN BISNIS DI ERA GLOBALISASI - Sunandar, Sunandar (Fokus Bisnis, 2014)
Management is the science and art. As a science, management has the general principles that are universal, but the art aspect of the application stage so that the color stands out overall managerial process. Hence the emergence of management style is a reflection of the adjustment application of the general principles of management of the environment in which the managerial process takes place. Management style in Japan, South Korea, China, United States and Indonesia have different advantages depending on factors such as the characteristics of employees, work activities involved in the organizational culture. In a further development excellence enrich the management style of management science it self